Late Holocene camelid pastoralism in the Puna highlands of Argentina: an integrative approach using stable isotope analysis of tooth enamel - Samec, Celeste T.; Yacobaccio, Hugo D.; Roberts, Patrick (Frontiers in Environmental Archaeology, 2025)
Pre-Hispanic pastoralist mobility has been a major topic in Andean archaeology and it is considered a key component of modern pastoral systems in the Andean highlands. Of particular interest here has been the exploration of changes in camelid breeding and herding between pre-Hispanic and modern pastoralist contexts. This paper examines variation in diet and territoriality of domestic camelids using intra-tooth enamel carbon and oxygen stable isotope measurements from modern and archaeological llama specimens from the Dry Puna of Argentina. We explore whether dietary and territoriality changes linked to seasonal mobility of modern llama herds are reflected in intra-tooth isotopic variation, and thus establish a modern frame of reference to study Late Holocene pastoralist mobility in the Puna highlands. Our preliminary results show the existence of moderate intra-tooth isotopic variation for enamel δ13CV − PDB and δ18OV − PDB values. Seasonal changes in plants and water consumed throughout the year dictated by the alternation of different pasture areas do not translate into significant isotopic variation for the modern camelid specimens analyzed. Moreover, intra-tooth series of archaeological camelid specimens show a similar patterning. This exposes the limitations of using carbon and oxygen stable isotope compositions measured in sequentially sampled camelid teeth to identify pastoralist mobility patterns in the tropical highlands of the Andes. Nonetheless, the consistency of our results shows continuities between pre-Hispanic and modern pastoralist practices in the Dry Puna of Argentina.